THE EFFECTIVENESS OF CORN SILK EXTRACT AGAINST DENTAL CARIES-CAUSING BACTERIA AND ITS FORMULATION IN MOUTHWASH PREPARATION - Qariru, Davin Elian; Kar, Kevin Lensrich; Alfaqih, Muhammad Yusuf; Zahra, Aulia Putri Fatiya; Aulia, Rahma; Purwanto, Purwanto (Universitas Muhammadiyah Magelang, 2024)
Indonesia is undergoing a dental caries emergency with a prevalence of 51.1% (Riskesdas, 2018). This may cause tooth decay due to dental plaque bacteria such as Streptococcus mutans. Mouthwash can be a solution because it has antibacterial properties and reaches interspaces on the teeth. Unfortunately, the active ingredient of mouthwash, chlorhexidine, can cause cancer-related mutations if used continuously. Therefore, it requires alternatives to natural ingredients, such as corn silk. The research aims to determine the corn silk phytochemical profile and minimum inhibitory concentration (MIC) against Streptococcus mutans. The research started by macerating corn silk simplicia using 70% ethanol. Afterwards, thin layer chromatography (TLC) was conducted to determine its phytochemical profile. Disk-diffusion and broth microdilution methods were conducted using various concentrations of corn silk extract to determine its antibacterial activity and minimum inhibitory concentration (MIC) against Streptococcus mutans. Then, the MIC₅₀ was used as the minimum dose of corn silk extract concentration in mouthwash formulation which qualities controlled by pH and organoleptic tests. The yield of corn silk extracted was 16.17%w/w. The phytochemical profile from TLC showed that flavonoids, tannins, and terpenoids were present. Corn silk extract has antibacterial activities against Streptococcus mutans with MIC₅₀ of 7.2%w/v. Corn silk extract, tween 80, sorbitol, sodium benzoate, sodium metabisulfite, oleum menthae piperitae, and distilled water were used in four mouthwash formulas (F1-F4). The pH of all formulas was 5 and the organoleptic test showed that from 30 panelists, the majority chose F2 as the best in terms of taste, color, and smell.